Evaluation of Response Reduction Factor for Flat Slab Structures: - (Journal of Advances and Scholarly Researches in Allied Education, 2018)
According to Indian Standards while designing any earthquake resisting structure we consider two moment resisting frames i.e. ordinary moment resisting frame (OMRF) having response reduction factor 3 for low design base shear and special moment resisting frame (SMRF) having response reduction factor 5 for high design base shear. The objective of this project is to study the seismic behavior of flat slab system by evaluating ‗R‘ factor and by pushover analysis comparing the results with the frame structure. The parameters like base shear, storey displacement, storey drift, bending and shear stresses in column and slab etc. are studied by STAAD.Pro software in this project. Method of analysis used is Response Spectrum Method.